Directed differentiation of granular cells from crayfish hematopoietic tissue cells. Issue 88 (May 2019) - Li, Fang; Xu, Limei; Hui, Xuan; Huang, Wanzhen; Yang, Feng
Abstract: Hemocytes are the major immune cells of crustaceans. New hemocyte production is required throughout the life cycle of these animals to maintain a functional immune system. The mechanism of crustacean hematopoiesis has just begun to be understood and new methods are needed for the investigation of this process. Here we report the directed differentiation of granular cells (GCs) from the hematopoietic tissue (HPT) cells of Cherax quadricarinatus in vitro . We started by providing the cultured HPT cells with different additives to induce possible differentiation. We found that crayfish muscle extract greatly promoted the physical status of the cells and induced the formation of refractile cytoplasmic granules. The transcription of marker genes and the production of functional prophenoloxidase further confirmed the formation of mature GCs. In our experiments, young GCs usually started to develop in ∼2 weeks post induction and over 60% of the cells became mature within 3–4 weeks. This is the first time that the fully differentiation of crustacean hemocytes is accomplished in vitro . It provides a powerful tool for in-depth study of crustacean hematopoiesis. Highlights: Muscle extract induces efficient differentiation of granular cells from the hematopoietic tissue cells of crayfish. Over 60% of the induced hematopoietic tissue cells become granular cells within 3-4 weeks. We provide a powerful tool for in-depth study of crustacean hematopoiesis.